Impact of the Reggio Emilia Approach through short term study abroad and the lenses of Lundy's model: Space, voice, audience, and influence - Sandra H Seipel; Victoria Seeger (Educational Considerations, 2024)
This study examines undergraduate short-term study abroad to Reggio Emilia, a construct that values what children know and can create as capable learners, and its impact on novice teachers’ practices to learn what skills and abilities each had for allowing children to make decisions, have control in the classroom, and reduce compliance expectations. Data indicated a lack of confidence, support, and guidance for incorporating the philosophy within an American school setting. American schools’ focus on standards-based instruction, assessment aimed at increasing test scores, and lack of teacher-driven curriculum played significant roles in the participants’ inability to employ Reggio Emilia processes into their classroom settings. While Lundy’s model of including children in decision-making for space, voice, audience, and influence is used as a lens, the role of intentionality in what occurs in the Reggio Emilia setting is examined based on the participants’ responses in focus groups conducted by the researchers The research brings to light how children’s capacity to be learners is marginalized in American schools and what the role is of teacher preparation programs in disrupting the current educational system to value what teachers understand to be best practices for young children.
Keywords: study abroad; Reggio Emilia; space; voice; audience; influence